2004
DOI: 10.1074/jbc.m311392200
|View full text |Cite
|
Sign up to set email alerts
|

Rat Long Chain Acyl-CoA Synthetase 5, but Not 1, 2, 3, or 4, Complements Escherichia coli fadD

Abstract: Long chain fatty acids are converted to acyl-CoAs by acyl-CoA synthetase (fatty acid CoA ligase: AMP forming, E.C. 6.2.1.3; ACS). Escherichia coli has a single ACS, FadD, that is essential for growth when fatty acids are the sole carbon and energy source. Rodents have five ACS isoforms that differ in substrate specificity, tissue expression, and subcellular localization and are believed to channel fatty acids toward distinct metabolic pathways. We expressed rat ACS isoforms 1-5 in an E. coli strain that lacked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…We have shown earlier that inhibiting multiple ACS activities strongly induces apoptosis, whereas this cell death is almost completely suppressed by a single gene transfer of ACSL5 . In addition, among mammalian ACS, only ACSL5 restores the growth of an Escherichia coli strain that lacks FadD, the only known ACS enzyme in the E. coli (Caviglia et al, 2004). These observations suggest that among ACS members, ACSL5 could have a predominant function in cell survival.…”
Section: Discussionmentioning
confidence: 87%
“…We have shown earlier that inhibiting multiple ACS activities strongly induces apoptosis, whereas this cell death is almost completely suppressed by a single gene transfer of ACSL5 . In addition, among mammalian ACS, only ACSL5 restores the growth of an Escherichia coli strain that lacks FadD, the only known ACS enzyme in the E. coli (Caviglia et al, 2004). These observations suggest that among ACS members, ACSL5 could have a predominant function in cell survival.…”
Section: Discussionmentioning
confidence: 87%
“…Therefore, the activity of these enzymes will be affected by both lipid-lipid, lipidprotein and protein-protein interactions at the membrane water interface (19,33). A number of studies of the activity of the different forms of this family of enzymes have been reported, but we argue that the majority of such data should be evaluated very carefully.…”
Section: Conversion Of Non-polar To Powerful Detergent Molecules At Tmentioning
confidence: 99%
“…The activity of these enzymes is strongly dependent on their lipid environment. The presence of lipids enhance their activity and the lipid composition of the membranes in which the enzymes are measured has been reported to affect their activity (19,33). Rescue of acyl-CoA synthetase mutants by the mammalian forms were performed in both E. coli and S. cerevisiae strains.…”
Section: Challenges In Measuring the Activity Of The Acsl Enzymesmentioning
confidence: 99%
“…Unique roles for ACS isoforms were first identified in studies of Saccharomyces cerevisiae mutants that lacked the ACS isoforms Faa1 and Faa4, and were unable to use exogenously provided fatty acids [31]. Similarly, complementation studies of ACS-deficient E. coli showed that each of the 5 rat ACSL isoforms differs in its ability to channel FA into specific pathways like phospholipid synthesis and β-oxidation [32]. The ACSL and FATP isoforms also differ in their ability to complement FA uptake and activation in mutated yeast strains that lack ACS activity [28,33].…”
Section: Role Of Acyl-coa Synthetases In Fa Channelingmentioning
confidence: 99%